(3fUGH GdGMJSGHs - (3GdSfGej, YeQ Hf eMeO YhV, J (B696 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdMSjH GdQbjH Ydi fhGdg EjeGfG hGMJSGHG hGdUdGI Ydi QShdg GdMHjH GdfSjH eMeO hBdg eGdG jMUi cJGHG hdG MSGHG LeY aj HMQ aVdg GdWGej YeQ aj JUGfja gPG GdcJGH hgh GdGMJSGH eSGFd GNJUJ HGdfSHI Edi MSH GdMSHI ef cJH eYJHQI s
(3BNQgG (B:s
(3hCNQL YeQ QVj Gddg Yfg adGfG Ydi GdfhM hEPG cGfJ GdeQCI ddJYRjI aJfhM Ydi GdejJ LYd jLhR ddeMJSH Cf jNQLgG ef HjJ ZjQg hde jMQLgG Cgdg Ce dG ? GdLhGH fYe Ef YeQ QVj Gddg Yfg CNQL CNJ CHj HcQ QVj Gddg Yfg ef HjJg Mjf fGMJ ef UMjM GdHNGQj hGddg CYde HGdUhGH hEdjg GdeQLY hGdeBH(B0s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5 / 63s
(3eYLe GdeDdajf (B2 / 577s
(3cTa GdXfhf (B2 / 1953s
(3TPQGJ GdPgH (B5 / 436s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs